Horizontal Cylindrical Structures in an Unconsolidated Quaternary Deposit at Saint-Joachim, Near Québec City (Canada) - Dionne, Jean-Claude; Laliberté, Simon (Géographie physique et Quaternaire, 2005)
AbstractTwo series of six horizontal cylindrical structures (pipes) were discovered recently in a Late Pleistocene (11‑10 ka BP) emerged delta deposit about 40 km NE of Québec City, Canada. The pipes occur at a depth of 19 m in a slightly oxydized layer of fine sand which is interlayered with two strata of compact blue silty clay, respectively 35 and 45 cm in thickness. The maximum length of the pipes is not known, but the remaining exhumed pipes measure 34 to 59 cm. Their diameter ranges from 6.5 to 14.5 cm. The pipe core generally consists of clean and loose medium to coarse sand whereas the outer ring, made of oxydized fine sand, is semi-consolidated. Pipes are the result of water flow in a permeable sand layer enclosed between two non-permeable layers; water enclosed in a shallow basin created by local collapsing was under hydraulic pressure and forced to drain out on the delta front. These water escape features are possibly the first known site of horizontal cylindrical structures observed in unconsolidated Quaternary sediments.